Transformation of Arabic Language Learning through Songs: A Reflective Autoethnographic Study At MTs Ihyaul Ulum Miru Gresik - Dewi, Metha Kusuma; Yusuf, Kamal (Raja Zulkarnain Education Foundation, 2025)
The purpose of this study is to explore: 1) teachers' reflective experiences can contribute to the development of Arabic language learning strategies Arabic language learning; 2) identify the impact of using songs on learning effectiveness; 3) explore the challenges teachers face in implementing this method. This research was conducted at MTs Ihyaul Ulum Miru Gresik in the odd semester of 2024/2025. The population in this study were ninth grade (IX) students at MTs Ihyaul Ulum Miru Gresik, the research sample was taken half of the six classes, namely classes AC. This study used a reflective autoethnography approach, in which the researcher reflected on personal experiences when applying the song method and observed its impact on student motivation and understanding. Data were collected through reflective journals, classroom observations, student interviews and analyzed using a thematic approach to identify patterns of experience, challenges and changes in teaching strategies. The results of this study showed that: 1) Teachers who conduct indepth selfreflection are able to develop more effective and contextualized learning strategies; 2) The use of songs in Arabic language learning at MTs Ihyaul Ulum Miru Gresik significantly has a positive impact on students' motivation, participation, and comprehension as well as helping to create a pleasant learning atmosphere, increase emotional involvement, and strengthen memory of vocabulary and sentence structure. In other words, songs are an effective innovation in transforming Arabic language learning; 3) The main challenges in the implementation of songbased learning include time constraints, diverse student responses, negative peer influences, technical constraints, and limited compatibility of materials with methods, which overall require teachers to be more flexible, reflective, and adaptive in maintaining a balance between creativity and academic needs.